Current perspectives on wearable rhythm recordings for clinical decision-making: the wEHRAbles 2 survey. Issue 7 (11th June 2021) - Manninger, Martin; Zweiker, David; Svennberg, Emma; Chatzikyriakou, Sofia; Pavlovic, Nikola; Zaman, Junaid A.B.; Kircanski, Bratislav; Lenarczyk, Radoslaw; Vanduynhoven, Philippe; Kosiuk, Jedrzej; Potpara, Tatjana; Duncker, David
Abstract: Novel wearable devices for heart rhythm analysis using either photoplethysmography (PPG) or electrocardiogram (ECG) are in daily clinical practice. This survey aimed to assess impact of these technologies on physicians' clinical decision-making and to define, how data from these devices should be presented and integrated into clinical practice. The online survey included 22 questions, focusing on the diagnosis of atrial fibrillation (AF) based on wearable rhythm device recordings, suitable indications for wearable rhythm devices, data presentation and processing, reimbursement, and future perspectives. A total of 539 respondents {median age 38 [interquartile range (IQR) 34–46] years, 29% female} from 51 countries world-wide completed the survey. Whilst most respondents would diagnose AF (83%), fewer would initiate oral anticoagulation therapy based on a single-lead ECG tracing. Significantly fewer still (27%) would make the diagnosis based on PPG-based tracing. Wearable ECG technology is acceptable for the majority of respondents for screening, diagnostics, monitoring, and follow-up of arrhythmia patients, while respondents were more reluctant to use PPG technology for these indications. Most respondents (74%) would advocate systematic screening for AF using wearable rhythm devices, starting at patients' median age of 60 (IQR 50–65) years. Thirty-six percent of respondents stated that there is no reimbursement for diagnostics involving wearable rhythm devices in their countries. Most respondents (56.4%) believe that costs of wearable rhythm devices should be shared between patients and insurances. Wearable single- or multiple-lead ECG technology is accepted for multiple indications in current clinical practice and triggers AF diagnosis and treatment. The unmet needs that call for action are reimbursement plans and integration of wearable rhythm device data into patient's files and hospital information systems. Graphical Abstract: